Climate change impacts on south African non-life insurance: A comprehensive analysis of natural disaster risk and adaptation strategies - Buthelezi, Sandile Johannes; Hungwe, Taurai; Mbirimi-Hungwe, Vimbai; Seeletse, Solly Matshonisa (Edelweiss Applied Science and Technology, 2025)
This study investigates the impact of climate change on the South African insurance industry, focusing specifically on the increased frequency and intensity of natural disasters. The escalating threats posed by extreme weather events, including floods, droughts, storms, and wildfires, are analyzed in depth, revealing a significant surge in damages related to property, business interruptions, and agricultural losses. As weather patterns become increasingly unpredictable, the study highlights the challenges faced by South Africa in predicting and managing risks effectively, necessitating a paradigm shift in risk assessment methodologies. Descriptive statistics and time series analyses were used to summarize and observe trends over the period 2000-2024 to provide a comprehensive examination of the intricate relationship between climate change and the South African insurance industry, focusing on the escalating risks posed by natural disasters. The study reveals that droughts are the most significant climatological concern in South Africa, with hydrological disasters being the most common. Meteorological disasters are more frequent, emphasizing the need for robust preparedness and response measures. Floods are the most prevalent disaster type, with KwaZulu-Natal having the highest number of disasters. The Eastern Cape and Northern Cape experience fewer disasters. Overall, climatological, hydrological, and meteorological events are the most prevalent, with droughts dominating the climatological subgroup. This comprehensive analysis contributes to the growing body of knowledge on the intersection of climate change and the insurance industry in South Africa, providing insights into the multifaceted challenges insurers face and outlining potential adaptation strategies. The findings of this study offer valuable guidance for industry stakeholders, policymakers, and researchers seeking to navigate the complex landscape of climate-related risks in the insurance sector.